Conscientiousness and engagement with national health behaviour guidelines. Issue 4 (21st April 2021) - Gartland, Nicola; Wilson, Antonia; Lawton, Rebecca; O'Connor, Daryl B.
ABSTRACT: High conscientiousness is associated with better health and longer life. This relationship is partly accounted for by the performance of health behaviours. The current study aimed to investigate whether conscientiousness was associated with adherence to national health behaviour guidelines as an indicator of healthy lifestyle. A cross-sectional design was used, where participants ( N = 886) completed online questionnaires to assess conscientiousness and the facets of conscientiousness (order, virtue, traditionalism, self-control, responsibility, industriousness) and the performance of four health behaviours (fruit and vegetable consumption, alcohol intake, smoking, and physical activity). An index was calculated to combine the health behaviours. Conscientiousness and all its facets significantly predicted the health behaviour guideline index. In comparing high and low conscientious sub-groups, the low conscientious group had lower levels of adherence to all health behaviours guidelines measured. Strikingly, the number of high conscientious participants meeting all health behaviour guidelines was nearly twice the number of low conscientious participants meeting all guidelines. Conscientiousness is associated with adherence to multiple national health behaviour guidelines. Therefore, the positive associations between conscientiousness and health/longevity may be accounted for, in part, by the adoption of a healthy lifestyle across multiple health domains.